Effect of Addition of Ethanol Extract from Sijukkot Leaves (Lactuca Indica L.) on Cholesterol Reduction in Male Strain Rats (Rattus Norvegicus) - Felivia Angelina Munte; Albinus Silalahi (Indonesian Journal of Chemical Science and Technology (IJCST), 2022)
Cholesterol is one of the lipids that can form cell membranes and extremity layers and functions as a lipoprotein compound. Rising cholesterol levels can cause various diseases. The leaves of the sijukkot plant have been used as a lowering of cholesterol levels in the body. By using SPSS analysis, it was found that the Shapiro-Wilk Normality Test with a sig value > 0.05, the data were normally distributed. The results of the analysis in the Test of Homogeneity of Variances table obtained a Sig value of 0.510. Thus the value of Sig = 0.510 > 0.05, then Ho is accepted. Thus, the ethanol extract of sijukkot leaves has the potential to reduce cholesterol levels. By using four different doses, the rat group at a dose of 100 mg/kgBW showed cholesterol levels of 77.25 (mg/dL) ± 9.14, the rat group at a dose of 200 mg/kgBW showed cholesterol levels of 62.75 (mg/dL) ± 5.44, the rat group at a dose of 200 mg/kgBW showed a cholesterol level of 62.75 (mg/dL) ± 5.44. 300 mg/kgbw showed a cholesterol level of 61.50 (mg/dL) ± 4.1 and a group of rats at a dose of 400 mg/kgbw showed a cholesterol level of 54.50 (mg/dL) ± 4.1